2021
DOI: 10.3390/su14010278
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Innovation Design in Catering Service

Abstract: COVID-19 has impacted the whole world since 2019, especially the dietary patterns of customers. Before the pandemic, some companies had been monitoring the operation data for health and food safety situations. It has become a vital mission to improve the food production and service process if the companies wish to pursue the sustainability of their businesses due to the general environment being changed by the epidemic. The sustainability of food systems inherently implies not only customer satisfaction but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Sustainability in restaurants has emerged as both an environmental and financial imperative, leading to the adoption of service innovation and sustainable practices as effective means to achieve this goal, as highlighted in the literature (Schubert et al ., 2010; Chou et al ., 2016; Yoon et al ., 2020; van Riel et al ., 2021; Chung et al ., 2022). However, it is observed that different restaurant profiles exist in terms of their approaches to sustainable service, and this study aims to identify these profiles in the decision-making of restaurant owners and/or managers regarding sustainable practices associated with each profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainability in restaurants has emerged as both an environmental and financial imperative, leading to the adoption of service innovation and sustainable practices as effective means to achieve this goal, as highlighted in the literature (Schubert et al ., 2010; Chou et al ., 2016; Yoon et al ., 2020; van Riel et al ., 2021; Chung et al ., 2022). However, it is observed that different restaurant profiles exist in terms of their approaches to sustainable service, and this study aims to identify these profiles in the decision-making of restaurant owners and/or managers regarding sustainable practices associated with each profile.…”
Section: Discussionmentioning
confidence: 99%
“…Gastronomy plays a significant role in motivating consumers (Seyitoğlu and Ivanov, 2020), who are increasingly interested in exploring local produce, experiencing culinary innovations and embracing sustainable practices (Daries et al ., 2021). Continuous improvement in restaurant operations is essential for customer satisfaction, the sustainability of the food system and cost-saving for businesses (Chung et al ., 2022). Consequently, researchers, industry professionals and policymakers have demonstrated a growing interest in service innovation as a business approach to address sustainability challenges (Calabrese et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the risk assessment, this study sets mathematical symbols for the calcu- The Kano model divides the differences of consumer demands in detail, surpasses the linear relationship between quality and satisfaction, and presents the changes of consumer demand dynamically. Thus, due to its excellent performance in depicting consumers' real ideas, it has been widely used in product design, enterprise management, service optimization, and other fields [53,54]. As service quality is widely concerned by consumers, applying the Kano model to the service reliability optimization of SSEVs definitely contribute to a more comprehensive and efficient service improvement.…”
Section: Methodsmentioning
confidence: 99%
“…High service quality, according to the results, increases staff happiness and retention, which in turn decreases training expenses and boosts operational efficiency. Additionally, A sustainable innovation design framework for catering service quality has been proposed by [5]. This delves into the correlation between conventional catering companies' financial success and the quality of their services.…”
Section: Review Of Literaturementioning
confidence: 99%